Green recovery of vanadium from vanadium-bearing shale under the biological action by Bacillus mucilaginosus and its effect on mineral dissolution. Issue 1 (February 2022) - Wang, Yue; Cai, Zhenlei; Zhang, Yimin; Zheng, Qiushi
Abstract: The recovery and utilization of vanadium from vanadium-bearing shale is significant, because vanadium is an important strategic metal. In this study, the method for extracting vanadium by Bacillus mucilaginosus was proposed to realize the green recovery of vanadium in vanadium-bearing shale. The optimal conditions for the recovery of vanadium and the phase transformation of vanadium-bearing shale under biological action were investigated. The results showed that the leaching efficiency of vanadium reached 54.2% after 30 days of bioleaching under the optimal conditions of 1 g/L yeast dip powder, which was 33.3% higher than that of the blank group. It was found by FTIR that metabolites such as EPS could adhere to the mineral surface and was gradually consumed over time. The semi-continuous experiment improved the metabolic activity of bacteria, and the released EPS further enhanced the bioleaching effect, in which the leaching efficiency of vanadium increased to 59.1% at 30 days and 61.7% at 50 days. The combined action of bacteria and metabolites removed the hydroxyl group of vanadium-bearing muscovite, further destroyed the basic structure of silicon-oxygen tetrahedron and aluminum oxygen octahedron, resulting in the release of vanadium from the crystal lattice. The recovery of vanadium under biological action could serve as a technical reserve for the green utilization of vanadium-bearing shale in the future. Graphical Abstract: ga1 Highlights: Yeast dip powder has the best promotion effect on bioleaching V. Determined the best process for B.M to extract V from vanadium-bearing shale. Semi-continuous process improved the activity of B.M in the process of V extraction. EPS enhanced the destruction of vanadium-bearing muscovite structure by B.M.